ARSITEKTUR RIGI-RIGI DERMATOGRAF DARI MARGA HYLOBATES DAN SYMPHALANGUS (FAMILI HYLOBATIDAE) DI INDONESIA - Maryanto, Ibnu; Kartono, Agus Priyono; Putro, Gembong IR Sunarto (JURNAL BIOLOGI INDONESIA, 2017)
ABSTRACTThe analysis of palm and sole arschitexture dermatographic traits have been done for two sub genera of Hylobates and Symphalangus in Indonesia. A dermatographical study was conducted to specimens from Indonesia Archipelago on genera Hylobates and Symphalangus, which are deposited in Museum Zoologicum Bogoriense-LIPI. A total of 101 specimens of Hylobates (78 specimens) and Symphalangus (23 specimens) were examined on palm and sole dermatographic traits. The discriminant canonical analyses showed that the Indonesian gibbon has two differences in function space of dermatograph types. By plotting these data, the percentage of the two groups that correctly classified was calculated to be 90.63%. Only nine specimens of Hylobates and Symphalangus were incorrectly classified, seven (9.5%) specimens Hylobates were classified as Symphalangus, and two specimens Symphalangus (9.1%) were classified as Hylobates. The majority of loops type dermatograph in this study indicated that the traits direction to ulnar, radial, and proximal between Hylobates and Symphalangus are significantly different (X2 >0.05, df=3; X2 = 13.58, 10.03 and 7.91 respectively).Keywords: Architecture Dermatographic, Hylobates, Symphalangus